Transnational Cybercrime: A Case Study of Indian Phone Scammers and Their Impact on International Security - Putri, Fannissa Melya; Lubis, Flori Mardiani; Marsingga, Prilla (Peneliti.net, 2025)
The rapid advancement of information and communication technology has given rise to increasingly sophisticated cybercrimes, one of which is transnational phone scams. This paper explores the emergence and operation of scam call centers, particularly those based in India, which target individuals in countries such as the United States, United Kingdom, and Canada. These scams not only result in significant financial losses but also undermine public trust in digital communication systems. Through a multidisciplinary analysis incorporating criminological theory and international cybercrime frameworks, this paper examines the structural, technological, and socio-economic factors enabling the persistence of such crimes. Furthermore, it proposes a set of policy implications, including the enhancement of international cooperation, regulatory reforms on data protection, public awareness initiatives, and improvements in law enforcement capacity. By addressing the issue from both global and local perspectives, this study aims to contribute to a more integrated and effective response to cyber-enabled fraud. The findings highlight the urgent need for transnational policy harmonization and collaborative enforcement mechanisms to counter the evolving threat of global phone scam operations.